2020
DOI: 10.1117/1.nph.7.4.045004
|View full text |Cite
|
Sign up to set email alerts
|

Task-related brain activity and functional connectivity in upper limb dystonia: a functional magnetic resonance imaging (fMRI) and functional near-infrared spectroscopy (fNIRS) study

Abstract: Significance: Dystonia is a dynamic and complex disorder. Real-time analysis of brain activity during motor tasks may increase our knowledge on its pathophysiology. Functional near-infrared spectroscopy (fNIRS) is a noninvasive method that enables the measurement of cortical hemodynamic activity in unconstrained environments. Aim: We aimed to explore the feasibility of using fNIRS for the study of task-related brain activity in dystonia. Task-related functional magnetic resonance imaging (fMRI) and restingstat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For dystonia, 46 articles were included, ( Zhang et al, 2020 , Pan et al, 2019 , Jochim et al, 2018 , Putzel et al, 2018 , Mantel et al, 2018 , Ni et al, 2017 , Huang et al, 2017 , Li et al, 2017 , Long et al, 2017 , Haslinger et al, 2017 , Kiyuna et al, 2017 , Battistella et al, 2016 , Sarasso et al, 2020 , Liu et al, 2016 , Ren et al, 2015 , Bharath et al, 2015 , Dresel et al, 2014 , Delnooz et al, 2015 , Hinkley et al, 2013 , Delnooz et al, 2013 , Delnooz et al, 2012 , Mohammadi et al, 2012 , Wei et al, 2021 , Jiang et al, 2019 , Pan et al, 2021 , Feng e al., 2021 , de Faria et al, 2020 , Norris et al, 2020 , Glickman et al, 2020 , Mantel et al, 2020 , Ma et al, 2021 , Corp et al, 2019 , Fang et al, 2021 , Giannì et al, 2022 , Qin et al, 2019 , Zito et al, 2022 , Kim et al, 2022 , Hou et al, 2022 , Ekmen et al, 2022 , Nieuwhof et al, 2022 , Filip et al, 2022 , Battistella and Simonyan, 2019 , Bianchi et al, 2019 , Kita et al, 2018 , Fuertinger and Simonyan, 2018 , Qin et al, 2018 ) concerning cervical dystonia (CD; n = 14), writer’s cramp (n = 10), laryngeal dystonia (n = 8), musician's dystonia (n = 5), paroxysmal kinesigenic dyskinesia (n = 6), blepharospasm (n = 6), oromandibular dystonia (n = 2), dyskinetic cerebral palsy (n = 2), spastic cerebral palsy (n = 1), dystonic tremor (n = 1), and generalized dystonia (n = 1). Most studies matched patients and healthy participants for age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…For dystonia, 46 articles were included, ( Zhang et al, 2020 , Pan et al, 2019 , Jochim et al, 2018 , Putzel et al, 2018 , Mantel et al, 2018 , Ni et al, 2017 , Huang et al, 2017 , Li et al, 2017 , Long et al, 2017 , Haslinger et al, 2017 , Kiyuna et al, 2017 , Battistella et al, 2016 , Sarasso et al, 2020 , Liu et al, 2016 , Ren et al, 2015 , Bharath et al, 2015 , Dresel et al, 2014 , Delnooz et al, 2015 , Hinkley et al, 2013 , Delnooz et al, 2013 , Delnooz et al, 2012 , Mohammadi et al, 2012 , Wei et al, 2021 , Jiang et al, 2019 , Pan et al, 2021 , Feng e al., 2021 , de Faria et al, 2020 , Norris et al, 2020 , Glickman et al, 2020 , Mantel et al, 2020 , Ma et al, 2021 , Corp et al, 2019 , Fang et al, 2021 , Giannì et al, 2022 , Qin et al, 2019 , Zito et al, 2022 , Kim et al, 2022 , Hou et al, 2022 , Ekmen et al, 2022 , Nieuwhof et al, 2022 , Filip et al, 2022 , Battistella and Simonyan, 2019 , Bianchi et al, 2019 , Kita et al, 2018 , Fuertinger and Simonyan, 2018 , Qin et al, 2018 ) concerning cervical dystonia (CD; n = 14), writer’s cramp (n = 10), laryngeal dystonia (n = 8), musician's dystonia (n = 5), paroxysmal kinesigenic dyskinesia (n = 6), blepharospasm (n = 6), oromandibular dystonia (n = 2), dyskinetic cerebral palsy (n = 2), spastic cerebral palsy (n = 1), dystonic tremor (n = 1), and generalized dystonia (n = 1). Most studies matched patients and healthy participants for age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely used in the field of neuropsychiatry and has great potential in the study of PD ( Ferrari and Quaresima, 2012 ). In fact, several studies using both fNIRS and fMRI have confirmed the effectiveness and reliability of fNIRS and emphasized its potential in the study of dystonia and other movement disorders ( Duan et al, 2012 ; Pierro et al, 2014 ; de Faria et al, 2020 ; Husain et al, 2020 ). Task-state fNIRS research focuses on inducing neural activity and locating related functional brain regions through specific activation.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 fNIRS can potentially study movement disorders such as PD as it can overcome movement restrictions and enable experiments in more natural conditions. 9 Focusing specifically on fine motor skills, fNIRS has been used to discriminate between different motor responses and levels of motor complexity, making it a relevant tool for monitoring changes related to fine motor skills. 10 In addition, fNIRS is a promising approach to studying the presumed contribution of dysfunction within the pre-frontal cortex (PFC) to difficulties in PD patients.…”
Section: Introductionmentioning
confidence: 99%